2003
DOI: 10.1093/emboj/cdg535
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulators for Plk1 activation in starfish meiotic and early embryonic cycles

Abstract: The Polo-like kinase, Plk, has multiple roles in regulating mitosis. In particular, Plk1 has been postulated to function as a trigger kinase that phosphorylates and activates Cdc25C prior to the activation of cyclin B-Cdc2 and thereby initiates its activation. However, the upstream regulation of Plk1 activation remains unclear. Here we have studied the interplay between Plk1 and Cdc2 through meiotic and early embryonic cycles in starfish. Distinct kinases, cyclin B-Cdc2, MAPK along with cyclin B- and/or cyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 42 publications
6
69
4
Order By: Relevance
“…Indeed, Plk1 can phosphorylate and thereby regulate both Cdc25C (12) and the Cdk1 inhibitor Myt1 (13,14). This would seem consistent with the hypothesis that Plk1 is the ''trigger'' kinase for the activation of Cdk1.…”
supporting
confidence: 57%
“…Indeed, Plk1 can phosphorylate and thereby regulate both Cdc25C (12) and the Cdk1 inhibitor Myt1 (13,14). This would seem consistent with the hypothesis that Plk1 is the ''trigger'' kinase for the activation of Cdk1.…”
supporting
confidence: 57%
“…It is involved in regulating multiple biological events in cancer cell proliferation [14]. In recent years, Plk1 has been discovered to also play regulatory roles in germ cells and oocytes, such as mouse [18], porcine [19], and starfish [20]. The recent focus of research has been on some Bexperimental or model^animals, such as Drosophila melanogaster [21], zebrafish [2], and mice [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies (42,43) have shown that Plk1 is implicated in a positive feedback loop that consists of both Plk1 and CDK1, and it does not function as the initial activator, rather its activation depends upon CDK1 activity. Our study seems to shed new light on this controversial issue, as the inhibitory effect of olomoucine on Plk1-mediated B23 Ser-4 phosphorylation that we observed here strongly implies that the B23 phosphorylation activity of Plk1 during M-phase is dependent upon CDK1 activation.…”
Section: Discussionmentioning
confidence: 99%